New Unsaturated Fatty Acid from Roots of Bougainvillea spectabilis Willd. - SINGH, SUMITRA; K. REDDU, SANJAY; K. SHARMA, SURENDRA; ALI, MOHAMMAD (Asian Journal of Chemistry, 2010)
A rare phosphoglycerol, phytoalcohol and a new unsaturated fatty acid were isolated from ethanolic extract of roots of Bougainvillea spectabilis Willd (Nyctaginaceae). The structures of these compounds were established on the basis of the detailed chemical reaction and spectral analysis as 1,2-dipalmitoleoyl glyceryl phosphate (1), n-henetriacontanol (2) and n-octacos-9-enoic acid (3).